A shape grammar for the spontaneous occupation settled in fishing villages: The case of Garopaba, Brazil. (March 2023) - Correa, Sara Dotta; Verzola Vaz, Carlos Eduardo
This work presents the second stage of a larger study which conducted the elaboration of a shape grammar based on the analysis of the remaining fishing villages in the Santa Catarina State, Southern Brazil. The architectural and formal structure of the villages provide a perspective of the constructive methods and features embedded in the spatial arrangements and represent a local cultural heritage site. The aim of the present work relies on unraveling its spatial resources using a shape grammar approach, in order to contribute to the preservation of a distinct culture, and is intended to be used to safeguard its formal language planning. Also, through the analytical grammar, it would be possible to contribute in framing design guidelines regarding the remaining villages, to keep it steady on the traditional context, safeguarding its peculiar character. As such, the method in this body of work considered the analysis resulting from the first stage, in order to develop an analytical shape grammar using Garopaba village as a case of study. This stage involved the establishment of a formal language for the analytical grammar, consisting of initial form, vocabulary, families, and spatial relations, and thus, a series of rules emerged, decoding the composition arrangements. The results involved the verification of the considered parameters, confirming the existence of spatial patterns. Thus, it was possible to conclude that the grammar contributes to identifying the occupation process occupation and the spatial patterns which underlies an artisanal fishing village. Also, the grammar allowed the creation of urban compositions similar to the structure of traditional fishing communities in Santa Catarina, generating different discussions regarding the analytical approach towards fishing villages arrangements, compared to the examples studied, specifically, in Garopaba city.